Tortillas fuera del comal - sistemas agrícolas y alimentarios resilientes al clima para Centroamérica (TOR2)​ - Gonzalez, Carlos R; Eitzinger, Anton; Navarro, Carlos; Castillo, Johana (2025)
The TOR2 study assesses how climate change affects the suitability of key crops such as maize and beans in Central America and identifies increasing risks from extreme weather events. It explores the potential for agricultural diversification with 30 crops and generates detailed local-scale spatial data to support adaptation decision-making.